Determining of the soil strength characteristics through the plate bearing test - Pantelidis, Lysandros (My University, 2008)
In the international literature there is often a confusion between the terms Modulus of Elasticity, EYoung, and Modulus of Deformation, EDef which is sometimes plainly referred to as Modulus E. In this paper the definitions of both the EYoung and the EDef have been clarified. Moreover, a soil classification diagram has been derived based on numerical analysis through a finite element software where soils are classified according to their shear strength parameters (c, φ) and their behavior under loads generated using a rigid circular bearing plate. Finally, a method for the determination of shear strength parameters, as well as the EYoung of soils has been proposed using the insitu Plate Bearing Test and solving a 3x3 mathematical system. The study and documentation of the proposed method is supported through three theoretical examples.
Keywords: Plate bearing test; Modulus of elasticity; Modulus of deformation; Cohesion; Internal friction angle